Lower limb hyperthermia augments functional hyperaemia during small muscle mass exercise similarly in trained elderly and young humans - Nuno Koch Esteves; Ashraf W. Khir; José González‐Alonso (Experimental Physiology)
Abstract Heat and exercise therapies are recommended to improve vascular health across the lifespan. However, the haemodynamic effects of hyperthermia, exercise and their combination are inconsistent in young and elderly people. Here we investigated the acute effects of local‐limb hyperthermia and exercise on limb haemodynamics in nine healthy, trained elderly (69 ± 5 years) and 10 young (26 ± 7 years) adults, hypothesising that the combination of local hyperthermia and exercise interact to increase leg perfusion, albeit to a lesser extent in the elderly. Participants underwent 90 min of single whole‐leg heating, with the contralateral leg remaining as control, followed by 10 min of low‐intensity incremental single‐leg knee‐extensor exercise with both the heated and control legs. Temperature profiles and leg haemodynamics at the femoral and popliteal arteries were measured. In both groups, heating increased whole‐leg skin temperature and blood flow by 9.5 ± 1.2°C and 0.7 ± 0.2 L min−1 (>3‐fold), respectively (P < 0.0001). Blood flow in the heated leg remained 0.7 ± 0.6 and 1.0 ± 0.8 L min−1 higher during exercise at 6 and 12 W, respectively (P < 0.0001). However, there were no differences in limb haemodynamics between cohorts, other than the elderly group exhibiting a 16 ± 6% larger arterial diameter and a 51 ± 6% lower blood velocity following heating (P < 0.0001). In conclusion, local hyperthermia‐induced limb hyperperfusion and/or small muscle mass exercise hyperaemia are preserved in trained older people despite evident age‐related structural and functional alterations in their leg conduit arteries.